2017
DOI: 10.1101/139782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cohesin loss eliminates all loop domains, leading to links among superenhancers and downregulation of nearby genes

Abstract: SUMMARY:The human genome folds to create thousands of intervals, called "contact domains," that exhibit enhanced contact frequency within themselves. "Loop domains" form because of tethering between two loci -almost always bound by CTCF and cohesin -lying on the same chromosome. "Compartment domains" form when genomic intervals with similar histone marks co-segregate. Here, we explore the effects of degrading cohesin. All loop domains are eliminated, but neither compartment domains nor histone marks are affect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 86 publications
(161 reference statements)
5
35
0
Order By: Relevance
“…Emergence of fine compartmentalization, however, was not reported likely due to the limited number of nuclei. Two other preprints reporting degron-mediated depletion of Rad21/Scc1 in human cell lines observed concordant effects on TADs, peaks, and compartmentalization to our study 36,37 . Rao et al also identified intriguing emergent “loop” cliques enriched in super-enhancers upon cohesin depletion 37 .…”
Section: Cohesin Is Central To Chromosome Foldingsupporting
confidence: 81%
See 1 more Smart Citation
“…Emergence of fine compartmentalization, however, was not reported likely due to the limited number of nuclei. Two other preprints reporting degron-mediated depletion of Rad21/Scc1 in human cell lines observed concordant effects on TADs, peaks, and compartmentalization to our study 36,37 . Rao et al also identified intriguing emergent “loop” cliques enriched in super-enhancers upon cohesin depletion 37 .…”
Section: Cohesin Is Central To Chromosome Foldingsupporting
confidence: 81%
“…Two other preprints reporting degron-mediated depletion of Rad21/Scc1 in human cell lines observed concordant effects on TADs, peaks, and compartmentalization to our study 36,37 . Rao et al also identified intriguing emergent “loop” cliques enriched in super-enhancers upon cohesin depletion 37 . We also observed such features in our primary hepatocytes using a new Hi-C browser 38 , though we note that in both cases these patterns do not resemble the sharp cis -only focal patterns of CTCF-associated Hi-C peaks commonly referred to as loops 12 .…”
Section: Cohesin Is Central To Chromosome Foldingsupporting
confidence: 81%
“…Additionally, the cohesin complex has been found to associate with CTCF to aid in cohesin binding at enhancers (80). Interestingly, depletion of cohesin results in the elimination of chromatin loops, however there is little transcriptional effect (85). One debate that remains in the field is whether cohesin depletion eliminates TAD architecture (85, 92), or is solely limited to inter-TAD loops (93, 96, 124).…”
Section: Enhancers In Nuclear Architecturementioning
confidence: 99%
“…Interestingly, depletion of cohesin results in the elimination of chromatin loops, however there is little transcriptional effect (85). One debate that remains in the field is whether cohesin depletion eliminates TAD architecture (85, 92), or is solely limited to inter-TAD loops (93, 96, 124). Disruption of cohesin causes a downregulation of super-enhancer-regulated genes (48).…”
Section: Enhancers In Nuclear Architecturementioning
confidence: 99%
“…Since its inception in the current form (Rao et al, 2014), originally termed APA ("Aggregate Peak Analysis"), pile-up analysis has been used in numerous publications, both to analyse single-cell Hi-C data (Flyamer et al, 2017;Gassler et al, 2017;Nagano et al, 2017) and as a general way of quantifying feature strength (Fudenberg et al, 2016;Schwarzer et al, 2017;Bonev et al, 2017;Nora et al, 2017;McLaughlin et al, 2019;Rao et al, 2017;Díaz et al, 2018;Kruse et al, 2019;Abdennur et al, 2018;Rowley et al, 2019;Krietenstein et al, 2019;Hsieh et al, 2019). A visual interactive tool to semi-manually classify and pile-up predefined regions has also been developed (Lekschas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%